Measuring Community Resilience to Natural Hazards: The Natural Hazard Resilience Screening Index (NaHRSI)—Development and Application to the United States. Issue 12 (7th December 2018) - Summers, J. Kevin; Harwell, Linda C.; Smith, Lisa M.; Buck, Kyle D.
Abstract: Natural disasters often impose significant and long‐lasting stress on financial, social, and ecological systems. From Atlantic hurricanes to Midwest tornadoes to Western wildfires, no corner of the United States is immune from the threat of a devastating natural hazard event. Across the nation, there is a recognition that the benefits of creating environments resilient to adverse natural hazard events help promote and sustain county and community success over time. The challenge for communities is in finding ways to balance the need to preserve the socioecological systems on which they depend in the face of constantly changing natural hazard threats. The Natural Hazard Resilience Screening Index (NaHRSI; previously entitled Climate Resilience Screening Index) has been developed as an endpoint for characterizing county resilience outcomes that are based on risk profiles and responsive to changes in governance, societal, built, and natural system characteristics. The NaHRSI framework serves as a conceptual roadmap showing how natural hazard events impact resilience after factoring in county characteristics. By evaluating the factors that influence vulnerability and recoverability, an estimation of resilience can quantify how changes in these characteristics will impact resilience given specific hazard profiles. Ultimately, this knowledge will help communities identify potential areas to target for increasing resilience to natural hazard events. Plain Language Summary: NaHRSI (Natural Hazard Resilience Screening Index) is a tool for communities to evaluate their likely vulnerability and resilience acute meteorological events like hurricanes, tornadoes, droughts, floods, etc. The index has been applied to all counties of the United States and is comprised of five major parts examining risk of events, governance to address events, societal, built environment and natural environment attributes that will enhance recoverability for these types of events. Key Points: An index of resilience to acute weather events has been developed The index has been applied to all counties in the United States The application allows the comparison of resilience of counties and the selections of counties provided best lessons learned for county resilience improvement